2020
DOI: 10.21203/rs.3.rs-28736/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Quantitative EEG as a biomarker in mild cognitive impairment with Lewy bodies

Abstract: Objectives: To investigate using quantitative EEG (1) differences between patients with mild cognitive impairment with Lewy bodies (MCI-LB) and MCI with Alzheimer’s disease (MCI-AD) and (2) its utility as a potential biomarker for early differential diagnosis. Methods: We analyzed eyes-closed, resting state, high-density EEG data from highly phenotyped participants (39 MCI-LB, 36 MCI-AD, and 31 healthy controls). EEG measures included spectral power in different frequency bands (delta, theta, pre-alpha, alpha,… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 22 publications
(44 reference statements)
1
3
0
Order By: Relevance
“…Quantitative EEG findings of MCI-LB have been reported to be similar to those reported in DLB vs. AD, where MCI-LB have lower dominant frequency compared to MCI-AD [ 65 , 66 , 67 ]. This also translates into higher pre-alpha power and lower alpha and beta power and a higher theta/alpha ratio [ 65 , 66 , 67 ].…”
Section: Resultssupporting
confidence: 56%
See 3 more Smart Citations
“…Quantitative EEG findings of MCI-LB have been reported to be similar to those reported in DLB vs. AD, where MCI-LB have lower dominant frequency compared to MCI-AD [ 65 , 66 , 67 ]. This also translates into higher pre-alpha power and lower alpha and beta power and a higher theta/alpha ratio [ 65 , 66 , 67 ].…”
Section: Resultssupporting
confidence: 56%
“…AD, where MCI-LB have lower dominant frequency compared to MCI-AD [ 65 , 66 , 67 ]. This also translates into higher pre-alpha power and lower alpha and beta power and a higher theta/alpha ratio [ 65 , 66 , 67 ]. Schumacher 2020b reported that spectral power analyses had sensitivities of 23–51%, specificity of 81–97% and area under receiver operating characteristics curve (AUROC) of 0.54–0.71 in diagnosing MCI-LB ( Table 4 ) [ 67 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations